Repeated Systolic Anterior Motion of the Mitral Valve After Double Outlet Right Ventricle Repair - Junya Sugiura, MD; Hajime Sakurai, MD; Wataru Kato, MD; Keisuke Tanaka, MD; Koji Morita, MD; Koshi Yamaki, MD; Taisei Nagashima, MD (Annals of Thoracic Surgery Short Reports)
We herein report a rare case of double outlet right ventricle repair complicated by repeated systolic anterior motion of the mitral valve after weaning from cardiopulmonary bypass and postoperatively. Even in patients without obvious preoperative left ventricular outflow tract obstruction, systolic anterior motion and mitral regurgitation may still occur from functional factors, such as intraoperative or postoperative inotropic drug use, tachycardia, or intraventricular volume loss in patients with severe ventricular septal hypertrophy and left ventricular hypertrophy.